Beneficial effects of natural flavonoids on neuroinflammation - Chen, Yu; Peng, Fu; Xing, Ziwei; Chen, Junren; Peng, Cheng; Li, Dan (Frontiers in Immunology, 2022)
Neuroinflammation is the fundamental immune response against multiple factors in the central nervous system and is characterized by the production of inflammatory mediators, activated microglia and astrocytes, and the recruitment of innate and adaptive immune cells to inflammatory sites, that contributes to the pathological process of related brain diseases, such as Alzheimer’s disease, Parkinson’s disease, depression, and stroke. Flavonoids, as a species of important natural compounds, have been widely revealed to alleviate neuroinflammation by inhibiting the production of pro-inflammatory mediators, elevating the secretion of anti-inflammatory factors, and modulating the polarization of microglia and astrocyte, mainly via suppressing the activation of NLRP3 inflammasome, as well as NF-κB, MAPK, and JAK/STAT pathways, promoting Nrf2, AMPK, BDNF/CREB, Wnt/β-Catenin, PI3k/Akt signals and SIRT1-mediated HMGB1 deacetylation. This review will provide the latest and comprehensive knowledge on the therapeutic benefits and mechanisms of natural flavonoids in neuroinflammation, and the natural flavonoids might be developed into food supplements or lead compounds for neuroinflammation-associated brain disorders.